Alcohol withdrawal and the associated mood disorders-a review - Hui, Helena Lin Ngui; Siew, Audrey Foong Kow; Lai, Sally; Chau, Ling Tham; Yu, Cheng Ho; Ming, Tatt Lee (Multidisciplinary Digital Publishing Institute, 2022)
Recreational use of alcohol is a social norm in many communities worldwide. Alcohol use in moderation brings pleasure and may protect the cardiovascular system. However, excessive alcohol consumption or alcohol abuse are detrimental to one’s health. Three million deaths due to excessive alcohol consumption were reported by the World Health Organization. Emerging evidence also revealed the danger of moderate consumption, which includes the increased risk to cancer. Alcohol abuse and periods of withdrawal have been linked to depression and anxiety. Here, we present the effects of alcohol consumption (acute and chronic) on important brain structures—the frontal lobe, the temporal lobe, the limbic system, and the cerebellum. Apart from this, we also present the link between alcohol abuse and withdrawal and mood disorders in this review, thus drawing a link to oxidative stress. In addition, we also discuss the positive impacts of some pharmacotherapies used. Due to the ever-rising demands of life, the cycle between alcohol abuse, withdrawal, and mood disorders may be a never-ending cycle of destruction. Hence, through this review, we hope that we can emphasise the importance and urgency of managing this issue with the appropriate approaches.